miR-9-5p as a Regulator of the Androgen Receptor Pathway in Breast Cancer Cell Lines - Bandini, Erika; Fanini, Francesca; Vannini, Ivan; Rossi, Tania; Plousiou, Meropi; Tumedei, Maria Maddalena; Limarzi, Francesco; Maltoni, Roberta; Fabbri, Francesco; Hrelia, Silvana; Cho, William C. S.; Fabbri, Muller (Frontiers in Cell and Developmental Biology, 2020)
Breast cancer (BC) is the most diagnosed carcinoma and the leading cause of cancer death in female over 100 countries. Thanks to the advance in therapeutic strategies, patients’ survival has improved. However, the lack of response to treatments and drug resistance are still a main concern, demanding for new therapeutic approaches, in particular for the advanced stages of the disease. Androgen receptor (AR) is gaining increasing interest as a fourth targetable receptor in BC, however, its regulation in BC cells is still poorly understood. MicroRNAs (miRNAs) regulate gene expression post-transcriptionally. Here, we identified miR-9-5p as an inhibitor of AR expression, we validated the inverse correlation between miR-9-5p and AR in primary BC samples and we further identified a feedback loop in which androgen agonists of AR up-regulate miR-9-5p. We also provided evidence that miR-9-5p elicits anti-proliferative effects in BC cell lines regardless of their estrogen receptor status. Finally, we showed that miR-9-5p can revert AR-downstream signaling even in presence of AR-agonists, highlighting the role of this miR in the hormonal response of BC. In conclusion, this study supports the role of miR-9-5p as an anti-proliferative miR in BC and as a central modulator of AR-signaling response to circulating androgens in BC.